2018
DOI: 10.1016/j.devcel.2018.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Notch Signaling Pathway In Vivo Elicits Changes in CSL Nuclear Dynamics

Abstract: SummaryA key feature of Notch signaling is that it directs immediate changes in transcription via the DNA-binding factor CSL, switching it from repression to activation. How Notch generates both a sensitive and accurate response—in the absence of any amplification step—remains to be elucidated. To address this question, we developed real-time analysis of CSL dynamics including single-molecule tracking in vivo. In Notch-OFF nuclei, a small proportion of CSL molecules transiently binds DNA, while in Notch-ON con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
141
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(181 citation statements)
references
References 67 publications
10
141
0
Order By: Relevance
“…Firstly, the evidence indicates a much more dynamic association of CSL with DNA. The CSL-DNA binding affinity appears to be lower than previously measured (Friedmann & Kovall, 2010) and CSL kinetics in Notch off conditions, based on live-imaging experiments, are very dynamic with estimated residence at target sites of circa 1 s ( Figure 2b; Gomez-Lamarca et al, 2018). Second, in vitro measurements revealed that co-repressors and NICD have similar affinities for CSL, or even in some cases repressors have a higher affinity (Collins et al, 2014;Vanderwielen, Yuan, Friedmann, & Kovall, 2011;Yuan et al, 2016), suggesting that a simple subunit exchange would not be thermodynamically favorable, although it remains possible that other factors or protein modifications could modify the protein behaviors.…”
Section: Dynamics Of Dna Binding and Transcriptionmentioning
confidence: 51%
See 3 more Smart Citations
“…Firstly, the evidence indicates a much more dynamic association of CSL with DNA. The CSL-DNA binding affinity appears to be lower than previously measured (Friedmann & Kovall, 2010) and CSL kinetics in Notch off conditions, based on live-imaging experiments, are very dynamic with estimated residence at target sites of circa 1 s ( Figure 2b; Gomez-Lamarca et al, 2018). Second, in vitro measurements revealed that co-repressors and NICD have similar affinities for CSL, or even in some cases repressors have a higher affinity (Collins et al, 2014;Vanderwielen, Yuan, Friedmann, & Kovall, 2011;Yuan et al, 2016), suggesting that a simple subunit exchange would not be thermodynamically favorable, although it remains possible that other factors or protein modifications could modify the protein behaviors.…”
Section: Dynamics Of Dna Binding and Transcriptionmentioning
confidence: 51%
“…The CSL-DNA binding affinity appears to be lower than previously measured(Friedmann & Kovall, 2010)Gomez-Lamarca et al, 2018). In this model, CSL remained stably bound to DNA while the NICD exchange converted it from repression to activation.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…Moreover, once cleaved, NICD molecules move into the nucleus within minutes [4]. While several studies have focused on the mechanisms controlling Notch activation by ligand endocytosis [5][6][7][8][9], knowledge about the activation of Notch targets by cleaved NICD and the dynamics involved remains limited [10][11][12][13][14]. More broadly, the role of signal dynamics in controlling developmental processes and tissue differentiation is only partially understood [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%